2019
DOI: 10.1016/j.jval.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Decision Analysis to Support Health Technology Assessment Agencies: Benefits, Limitations, and the Way Forward

Abstract: Objective: Recent years have witnessed an increased interest in the use of multicriteria decision analysis (MCDA) to support health technology assessment (HTA) agencies for setting healthcare priorities. However, its implementation to date has been criticized for being "entirely mechanistic," ignoring opportunity costs, and not following best practice guidelines. This article provides guidance on the use of MCDA in this context. Methods:The present study was based on a systematic review and consensus developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(156 citation statements)
references
References 34 publications
1
153
0
2
Order By: Relevance
“…Specifically, we have added guidance on stakeholder participation 20 as well as guidance on how to use MCDA for HTA agencies, based on a recent consensus statement among more than 20 experts in the field. 21…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have added guidance on stakeholder participation 20 as well as guidance on how to use MCDA for HTA agencies, based on a recent consensus statement among more than 20 experts in the field. 21…”
Section: Discussionmentioning
confidence: 99%
“…Baltussen et al note that all three approaches to MCDA can improve the transparency of priority setting by providing explicit criteria against which health interventions are evaluated (4). Furthermore, they add that quantitative MCDA can enhance transparency compared to qualitative MCDA when the numerical weights and scores for these criteria and the mathematical aggregation function are explicitly reported to the public.…”
Section: On Transparency: More Than Disclosing Methods and Scoresmentioning
confidence: 99%
“…Finally, MCDA appraisal committees may simply overlook or shortchange deliberation when it is the last step of a long and complex process. Indeed, Baltussen et al found that only a minority of quantitative MCDA studies reported engaging in deliberation at all (4). Thus, to better promote the quality and transparency of appraisals, deliberation should be given a much more prominent role in appraisals through the adoption of qualitative MCDA.…”
Section: On Transparency: More Than Disclosing Methods and Scoresmentioning
confidence: 99%
“…Rather, MCDA should be a part of the broader domain of priority setting and resource allocation decisions where considerations of budget and opportunity cost occur concurrently. As such it may be helpful to distinguish between "qualitative" MCDA and "quantitative" MCDA (25). The former is described as a deliberative process that embeds the use of MCDA within larger discussions about overall affordability and value for money relative to the broader portfolio of investments.…”
Section: The Rise Of Multi-criteria Decision Analysis (Mcda) In Drug mentioning
confidence: 99%